2011
DOI: 10.1177/0032885511409893
|View full text |Cite
|
Sign up to set email alerts
|

Injecting Risk Into Prison Sentences

Abstract: This article draws on penal epidemiological studies to analyze data from a prisoner-driven survey measuring HCV/HIV seroprevalence and risk behaviors in one Canadian male prison. Our data illuminate confounding points of potential blood exchange among injectors and noninjectors, HCV/HIV carriers and noncarriers, tested and untested prisoners, and prison and free community members. The survey finds higher HCV/HIV incidence and testing rates among injectors, and a penal population educated about high-risk practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Bearing this out, a 2002 survey at the medium‐security research site showed that 100 of 224 (45%) prisoners who completed the survey self‐reported participating in penal tattooing. Of these, 56 were current or former penal injectors and 44 were non‐injecting prisoners (Bonnycastle and Villebrun, forthcoming).…”
Section: Methodsmentioning
confidence: 99%
“…Bearing this out, a 2002 survey at the medium‐security research site showed that 100 of 224 (45%) prisoners who completed the survey self‐reported participating in penal tattooing. Of these, 56 were current or former penal injectors and 44 were non‐injecting prisoners (Bonnycastle and Villebrun, forthcoming).…”
Section: Methodsmentioning
confidence: 99%